2020
DOI: 10.1027/1866-5888/a000262
|View full text |Cite
|
Sign up to set email alerts
|

Employee Strengths Use and Thriving at Work

Abstract: Abstract. This study aimed to investigate the relationship of employee strengths use with thriving at work by proposing a moderated mediation model. Data were collected at two time points, spaced by a 2-week interval. A total of 260 medical staff completed strengths use, perceived humble leadership, self-efficacy, and thriving scales. The results of path analysis showed that strengths use is positively related to thriving, and self-efficacy mediates the relationship of strengths use with thriving. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Other studies also support the ndings from this study, although, to the best of authors´ knowledge, this study is a pioneering research examining the proposed relationships among health professionals within the health services context. Consequently, our ndings extend the body of previous research on TAW within health services research that has previously been dominated by examining only the antecedents to TAW (e.g., 7,8,9,10,11,12) or only conceptually suggesting TAW to be associated with speci c outcomes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Other studies also support the ndings from this study, although, to the best of authors´ knowledge, this study is a pioneering research examining the proposed relationships among health professionals within the health services context. Consequently, our ndings extend the body of previous research on TAW within health services research that has previously been dominated by examining only the antecedents to TAW (e.g., 7,8,9,10,11,12) or only conceptually suggesting TAW to be associated with speci c outcomes.…”
Section: Discussionsupporting
confidence: 73%
“…The very few previous studies on TAW within health care settings have most often focused on the precursors to TAW. Examples of precursors include psychological capital and perceived organizational support [7], self-empowerment [8], autonomy [9], job satisfaction [10], self-e cacy [11], and job resources and job attachment [12]. Because of this one-sided focus we know very little about the potential outcomes of TAW.…”
Section: Introductionmentioning
confidence: 99%
“…Strengths use theory acknowledges that everyone has their own strengths (van Woerkom et al, 2016). By identifying, developing and using their own strengths at work, employees are prone to perform better and be more proactive (Ding & Chu, 2020). Recent studies suggest that strengths use can bring positive outcomes, for instance, thriving at work (Ding & Chu, 2020), organizational citizenship behaviour (Ding et al, 2020) and subjective well‐being (Jach et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By identifying, developing and using their own strengths at work, employees are prone to perform better and be more proactive (Ding & Chu, 2020). Recent studies suggest that strengths use can bring positive outcomes, for instance, thriving at work (Ding & Chu, 2020), organizational citizenship behaviour (Ding et al, 2020) and subjective well‐being (Jach et al, 2018). A study on public school teachers reported that strengths use was beneficial for reducing employees' turnover intention (Els et al, 2018), and a recent study of nurses found that strengths use was negatively related to nurses' depressive symptoms via basic psychological needs (Bai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thriving at work, as defined by Spreitzer et al (2005), is the psychological state in which individuals experience a sense of vitality coupled with learning at the workplace. Thriving is crucial energy for enabling healthy, high-performing and engaged employees, especially if an organization's goal is human sustainability (Spreitzer et al, 2012;Ding and Chu, 2020).…”
Section: Introductionmentioning
confidence: 99%